IMF Staff papers : Volume 35 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1988)
The proposal to set up an international debt facility to buy the debt of developing countries at a discount and then mark down its contractual value is analyzed. The paper considers the central question of how the debtor countries, creditor banks, and owners of the facility would be affected; in particular, what redistribution of gains and losses there would be among them. The "market price effect" and the "ceiling effect" are distinguished. A crucial consideration is whether debt retained by banks is subordinated to debt bought by the facility.